Prospects and challenges of hydrogen energy storage (HES) application: a review / Aizat Shazni Ahmad Umar … [et al.] - Ahmad Umar, Aizat Shazni; Sulaiman, Shahril Irwan; Abdul Rahman, Noor Hasliza; Ilham, Nur Iqtiyani (Universiti Teknologi MARA, 2021)
The hydrogen review gives an insight into the viability of hydrogen quickly being introduced as a primary energy and fuel carrier. Around the near future, hydrogen has been shown to have many advantages for the purposes set out in the paper, as well as few problems in use. The effective implementation of the hydrogen application brings numerous benefits to the atmosphere, energy protection, the economy, and end-users. Hydrogen is a key player in electricity storage, lost in large power grids by off-peak diversion to loads at the generation level. The world needed solutions as pollution in the atmosphere grew. Luckily, metal hydride-based solid-state storage systems have shown great potential for storing hydrogen in large quantities in a very safe, lightweight, and repeatedly reversible way, thus becoming an increasingly attractive choice for hydrogen applications. This paper also addresses the challenge levels of utilizing hydrogen for ICE(Internal Combustion Engine), storage and recommends different approach to address the poly generation system financials issues. Compared with doing the same in large-scale containers, storage in small to medium-sized containers is shown to be very economical. This paper provides a brief overview of hydrogen as the ideal renewable energy carrier for the future economy, its storage as the stumbling block, and the current role of solid-state hydrogen storage in metal hydrides, and deliver a recommendation based on the most promising recent novel developments in the area, indicating a possible turning point towards hydrogen.